Electromagnetic fields - Wangsness, Roald K. (John Wiley & Sons, 1986)
Vectors -- Coulomb's law -- The electric field -- Gauss' law -- The scalar potential -- Conductors in electrostatic fields -- Electrostatic energy -- Electric multipoles -- Boundary conditions at a surface of discontinuity -- Electrostatics in the presence of matter -- Special methods in electrostatics -- Electric currents -- Ampére's law -- The magnetic induction -- The integral form of ampére´s law -- The vector potential -- Faraday's law of induction -- Magnetic energy -- Magnetic multipoles -- Magnetism in the presence of matter -- Maxwell´s equations -- Scalar and vector potentials -- Systems of units-a guide for the perplexed -- Plane waves -- Reflection and refraction of plane waves -- Fields in bounded regions -- Circuits and transmission lines -- Radiation -- Special relativity -- Motion of charged particles -- Electromagnetic properties of matter.